Diagnostic criteria for Patulous Eustachian Tube: A proposal by the Japan Otological Society. Issue 1 (February 2018) - Kobayashi, Toshimitsu; Morita, Masahiro; Yoshioka, Satoshi; Mizuta, Kunihiro; Ohta, Shigeto; Kikuchi, Toshiaki; Hayashi, Tatsuya; Kaneko, Akihiro; Yamaguchi, Nobumasa; Hashimoto, Sho; Kojima, Hiromi; Murakami, Shingo; et al.
Abstract: Patulous Eustachian Tube (PET) is of increasing importance in otology. However, despite the abundance of diseases requiring a differential diagnosis from PET, such as superior semicircular canal dehiscence syndrome, perilymphatic fistula, acute low-tone sensorineural hearing loss, etc., there are currently no established diagnostic criteria for PET. In view of these circumstances, the Japan Otological Society (JOS) Eustachian Tube Committee proposed the diagnostic criteria for Patulous Eustachian Tube in 2012, in order to promote clinical research on PET. A revision was made in 2016, maintaining the original concept that the criteria should be very simple, avoid any contamination of "Definite PET" with uncertain cases. Moreover, it was also intended to minimize the number of cases that could be accidentally excluded even in the presence of some suspected findings ("Possible PET"). The criteria can be used by all otolaryngologists even without using the Eustachian tube function test apparatus. However, the use of such an apparatus may increase the chances of detecting "Definite PET". The algorithm for the diagnosis of PET using the criteria has also been described. The JOS diagnostic criteria for Patulous Eustachian Tube will further promote international scientific communication on PET.